Isolated Peak of Oxygen Ion Fraction in the Post‐Noon Equatorial F‐Region: ICON and SAMI3/WACCM‐X. Issue 9 (19th September 2021) - Park, Jaeheung; Huba, J. D.; Heelis, Roderick; Englert, Christoph
Abstract: In the equatorial region, the fraction of oxygen ions (O + ) in the topside ionosphere contains information on the source altitude of the plasma, which is controlled, in part, by the vertical plasma motion in the F‐region. Previous studies on this topic are restricted by limited coverage of local time, latitude, and season, leaving a significant knowledge gap in the distribution of the topside ionospheric composition. In this study, we statistically investigate the O + fraction measured by ICON/IVM over all the local time sectors and seasons at low‐/midlatitudes. For the first time, we have found that an isolated peak in the O + fraction emerges in the post‐noon equatorial region. The peak is most prominent during equinoxes, while during solstices it is connected to the O + fraction bulges in the local summer midlatitudes. Simulations with SAMI3 coupled with thermospheric parameters from WACCM‐X reproduce the peak of the O + fraction. The post‐noon equatorial peak can be explained by the net vertical motion of plasma consisting of transports either parallel or perpendicular to geomagnetic field lines. Key Points: Using ICON data, we report the statistics of the low‐/midlatitude F‐region O + fraction with an extensive coverage of local time (LT), magnetic latitude (MLAT), and season A latitudinally and zonally isolated peak of the oxygen ion (O + ) fraction emerges at the post‐noon equatorial region Simulations by SAMI3 using WACCM‐X thermospheric fields reproduce the peak of the observed O + fraction